Alcohol Use Disorders - Sumantri Oei, T.P.; Hasking, Penelope (Elsevier Inc., 2013)
Alcohol use disorders are highly prevalent and confer significant costs (both financial and social) on society. This chapter begins by defining alcohol use disorders and outlining the associated consequences. These include accidents and injury, health risks, psychological effects, and financial costs. Numerous theories have been proposed to explain the initiation and maintenance of alcohol use, and the development of alcohol use disorders. This chapter briefly presents pharmacological theories, explores the role of genetics in alcohol use disorders, and discusses gene–environment interactions. Behavioral and cognitive theories are presented. Social cognitive theory, incorporating elements of both behavioral and cognitive theories, is presented as a comprehensive model with utility in explaining a wide range of drinking behavior. Finally, pharmacological and psychosocial treatments for alcohol use disorders are presented.